2020
DOI: 10.1210/jendso/bvaa155
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Treatments for Polycystic Ovarian Syndrome Management in Adolescents

Abstract: Limited evidence on treatment options for polycystic ovarian syndrome (PCOS) has led to considerable variation in healthcare practices. We aimed to compare the effects of metformin and/or oral contraceptive pills (OCPs) in combination with pioglitazone, spironolactone, flutamide, and lifestyle interventions among adolescents aged 11-19 years with PCOS. Literature searches were performed in Medline, Embase, and the Cochrane Central Register of Controlled Trials from database inception through December 2018, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Moreover, PCOS is associated with different endocrine, metabolic, and reproductive traits including hyperandrogenism, hyperinsulinism, obesity, hyperlipidemia, type 2 diabetes mellitus, cardiovascular abnormalities, depression, anxiety, anovulation, oligo-ovulation, infertility, hirsutism, and acne [ 3 , 4 ]. This syndrome is so devastated that it can cause endometrial hyperplasia and subsequently the development of endometrial cancer [ 5 ]. Concurrently, the PCOS patients are also suffering from elevated levels of low-density lipoprotein (LDL), triglycerides, total cholesterol, and decreased level of high-density lipoprotein (HDL) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PCOS is associated with different endocrine, metabolic, and reproductive traits including hyperandrogenism, hyperinsulinism, obesity, hyperlipidemia, type 2 diabetes mellitus, cardiovascular abnormalities, depression, anxiety, anovulation, oligo-ovulation, infertility, hirsutism, and acne [ 3 , 4 ]. This syndrome is so devastated that it can cause endometrial hyperplasia and subsequently the development of endometrial cancer [ 5 ]. Concurrently, the PCOS patients are also suffering from elevated levels of low-density lipoprotein (LDL), triglycerides, total cholesterol, and decreased level of high-density lipoprotein (HDL) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until more research confirms the positive metabolic effect of SGLT-2 inhibitors in PCOS patients, the mainstream treatment option will be lifestyle intervention, metformin, and oral contraceptive pills[ 24 ]. However, this treatment strategy does not successfully address long-term cardiometabolic consequences of PCOS[ 48 ], so SGLT-2 inhibitors, due to their mode of action, emerge as a potential new treatment option for PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…This was compared to COC (20μg ethinyl estradiol plus 100 mg levonorgestrel), which was seen as effective only in 42% of the adolescents. There are no statistically significant benefits to using SP in menstruation regulation [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…This demonstrates that a low-dose spironolactone combination (SPIOMET) is more effective than COC at reducing dysglycemia. Al Khalifah et al reported dysglycemia outcomes were available for seven therapies across 10 RCTs (n = 639) [ 37 ]. The absolute incidence of dysglycemia was observed to be 57 per 100 patients among COC users (95 % [CI], 1-100 more patients), compared to a baseline risk of 24% among controls.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation